Sociocultural correlates of eating pathology in college women from US and Iran - Sahlan, Reza N.; Akoury, Liya M.; Habashy, Jessica; Culbert, Kristen M.; Warren, Cortney S. (Frontiers in Psychology, 2022)
Objective: The buffering role of the hijab as a protective factor against eating pathology has been questioned in countries where wearing the hijab is compulsory, such as Iran; and, cross-cultural comparisons of body image in Iranian and Western women are sparse. Consequently, we examined sociocultural correlates of eating pathology in US and Iranian women. Method: College women from the US (n = 709) and Iran (n = 331) completed the Eating Disorder Examination-Questionnaire (EDE-Q) and the Sociocultural Attitude Toward to Appearance Questionnaire-4 (SATAQ-4). Prior to examining main hypotheses, we evaluated whether the scales perform similarly (i.e., establish measurement invariance) by culture. Results: The EDE-Q and SATAQ-4 were not invariant by culture indicating that the scales performed differently across groups, so separate analyses were conducted in each sample. Thin-ideal internalization and pressures for thinness were significant positive predictors of eating pathology in both US and Iranian women. Conclusion: Both pressures for thinness and thin-ideal internalization appear to be relevant to eating pathology in women from both cultures. However, there may be important cross-cultural differences in the interpretation or experience of these constructs. Further understanding of this measurement non-invariance and the ways in which Iranian women may be uniquely impacted by Western values of appearance is a critical next step.